Pueraria lobata (Kudzu root) hangover remedies and acetaldehyde-associated neoplasm risk - McGregor, Neil R. (Alcohol (Fayetteville, N.Y.), 2007)
Recent introduction of several commercial Kudzu root ( Pueraria lobata) containing hangover remedies has occurred in western countries. The available data is reviewed to assess if there are any potential concerns in relationship to the development of neoplasm if these products are used chronically. The herb Pueraria has two components that are used as traditional therapies; Pueraria lobata, the root based herb and Pueraria flos, the flower based herb. Both of these herbal components have different traditional claims and constituents. Pueraria flos, which enhances acetaldehyde removal, is the traditional hangover remedy. Conversely, Pueraria lobata is a known inhibitor of mitochondrial aldehyde dehydrogenase (ALDH2) and increases acetaldehyde. Pueraria lobata is being investigated for use as an aversion therapy for alcoholics due to these characteristics. Pueraria lobata is not a traditional hangover therapy yet has been accepted as the registered active component in many of these hangover products. The risk of development of acetaldehyde pathology, including neoplasms, is associated with genetic polymorphism with enhanced alcohol dehydrogenase (ADH) or reduced ALDH activity leading to increased acetaldehyde levels in the tissues. The chronic usage of Pueraria lobata at times of high ethanol consumption, such as in hangover remedies, may predispose subjects to an increased risk of acetaldehyde-related neoplasm and pathology. The guidelines for Disulfiram, an ALDH2 inhibitor, provide a set of guidelines for use with the herb Pueraria lobata. Pueraria lobata appears to be an inappropriate herb for use in herbal hangover remedies as it is an inhibitor of ALDH2. The recommendations for its use should be similar to those for the ALDH2 inhibitor, Disulfiram.